18F-FDG PET/CT in Uterine Follicular Dendritic Cell Sarcoma. (30th October 2021) - Yang, Yuhua; Liu, Lisha; Lin, Juyi; Huang, Shengcai
Abstract: A 46-year-old woman presented with menorrhagia, abdominal distension, and neck mass for 3 months. Ultrasonography detected a large intra-abdominal mass and enlarged neck lymph nodes. Further 18 F-FDG PET/CT scan revealed lesions with intense 18 F-FDG avidity in abdominal cavity and neck. The patient underwent a biopsy of the uterine, and the diagnosis of uterine follicular dendritic cell sarcoma was finally achieved. After 6 cycles of CHOP-like chemotherapy, 18 F-FDG PET/CT showed complete metabolic and morphologic resolution for follicular dendritic cell sarcoma.